Local-scale forcing effects on wind flows in an urban environment: Impact of geometrical simplifications. Issue 170 (November 2017) - Ricci, A.; Kalkman, I.; Blocken, B.; Burlando, M.; Freda, A.; Repetto, M.P.
Abstract: Wind flow in urban areas is strongly affected by the urban geometry. In the last decades most of the geometries used to reproduce urban areas, both in wind-tunnel (WT) tests and Computational Fluid Dynamics (CFD) simulations, were simplified compared to reality in order to limit experimental effort and computational costs. However, it is unclear to which extent these geometrical simplifications can affect the reliability of the numerical and experimental results. The goal of this paper is to quantify the deviations caused by geometrical simplifications. The case under study is the district of Livorno city (Italy), called "Quartiere La Venezia". The 3D steady Reynolds-averaged Navier-Stokes (RANS) simulations are solved, first for a single block of the district, then for the whole district. The CFD simulations are validated with WT tests at scale 1:300. Comparisons are made of mean wind velocity profiles between WT tests and CFD simulations, and the agreement is quantified using four validation metrics ( FB, NMSE, R and FAC1.3 ). The results show that the most detailed geometry provides improved performance, especially for wind direction α = 240° (22% difference in terms of FAC1.3 ). Graphical abstract: Highlights: Wind-tunnel tests have been performed on a reduced-scale urban district. 3D steady-state RANS simulations have been performed for a single block of the reduced-scale urban district (as wind tunnel). 3D steady-state RANS simulations have been performed for the whole urban district (as wind tunnel). The modeling errors caused by geometrical simplifications have been quantified. The agreement between wind-tunnel and numerical results has been quantified using four validation metrics.